Novel hybrid of clay, cellulose, and thermoplastics. I. preparation and characterization of composites of ethylene-propylene copolymer - Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Applied Polymer Science, 2007)
{The present study is aimed to prepare hybrid materials by incorporating layered silicates and microcrystalline cellulose into thermoplastic polymer. Using ethylene-propylene (EP) copolymer as thermoplastic polymer matrix and maleated EP (MEP) copolymer as compatibilizer, three types of composites were prepared by (i) melt mixing of cellulose with thermoplastics [
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations